Peran Pemerintah Daerah Dalam Meningkatkan Kapabilitas Inovasi Daerah: Tinjauan Literatur Kritis Dalam Konteks Wilayah Asia - Wibisono, Eristian (Jurnal Khazanah Intelektual, 2024)
This literature review explores the role of local governments in enhancing local innovation capabilities in the context of Asian regions, and specifically identifies the challenges local governments face in this endeavor, as well as solutions to overcome these challenges. Using a systematic literature review approach, this study critiques selected articles that are highly dominated by studies in China in addition to Taiwan and South Korea. Over the past decade, studies on this topic have continued to emerge and be published in high quality publication sources. The results of the critical review of the selected articles show that the main role and challenge of local government in enhancing local innovation capability is highly dependent on the ability to manage various innovation resources. To overcome these challenges, local governments are encouraged to promote cooperation and collaboration with key stakeholders in the regional innovation system, namely universities and industry. This paper contributes to the growing literature on regional innovation policy and motivates the practice of place-based innovation policy in the context of Asian regions. Future research directions are encouraged to focus on a broader range of Asian regions or on specific innovation contexts that reflect the characteristics of Asian regions.